Interaction between epidermal growth factor receptor and C-C motif chemokine receptor 2 in the ovulatory cascade - Conte, J. G.; Tellechea, M. L.; Park, B.; Ballerini, M. G.; Jaita, G.; Peluffo, M. C. (Frontiers in Cell and Developmental Biology, 2023)
The epidermal growth factor receptor (EGFR) signaling pathway is one of the main pathways responsible for propagating the luteinizing hormone (LH) signal throughout the cumulus cells and the oocyte. Recently, we have proposed the C-C motif chemokine receptor 2 (CCR2) and its main ligand (monocyte chemoattractant protein-1, MCP1) as novel mediators of the ovulatory cascade. Our previous results demonstrate that the gonadotropins (GNT), amphiregulin (AREG), and prostaglandin E2 (PGE2) stimulation of periovulatory gene mRNA levels occurs, at least in part, through the CCR2/MCP1 pathway, proposing the CCR2 receptor as a novel mediator of the ovulatory cascade in a feline model. For that purpose, feline cumulus-oocyte complexes (COCs) were cultured in the presence or absence of an EGFR inhibitor, recombinant chemokine MCP1, and gonadotropins [as an inducer of cumulus-oocyte expansion (C-OE), and oocyte maturation] to further assess the mRNA expression of periovulatory key genes, C-OE, oocyte nuclear maturation, and steroid hormone production. We observed that MCP1 was able to revert the inhibition of AREG mRNA expression by an EGFR inhibitor within the feline COC. In accordance, the confocal analysis showed that the GNT-stimulated hyaluronic acid (HA) synthesis, blocked by the EGFR inhibitor, was recovered by the addition of recombinant MCP1 in the C-OE culture media. Also, MCP1 was able to revert the inhibition of progesterone (P4) production by EGFR inhibitor in the C-OE culture media. Regarding oocyte nuclear maturation, recombinant MCP1 could also revert the inhibition triggered by the EGFR inhibitor, leading to a recovery in the percentage of metaphase II (MII)-stage oocytes. In conclusion, our results confirm the chemokine receptor CCR2 as a novel intermediate in the ovulatory cascade and demonstrate that the EGFR/AREG and the CCR2/MCP1 signaling pathways play critical roles in regulating feline C-OE and oocyte nuclear maturation, with CCR2/MCP1 signaling pathway being downstream EGFR/AREG pathway within the ovulatory cascade.